2017
DOI: 10.1038/s41598-017-17487-8
|View full text |Cite
|
Sign up to set email alerts
|

Heat-killed Lactobacillus casei confers broad protection against influenza A virus primary infection and develops heterosubtypic immunity against future secondary infection

Abstract: Lactic acid bacteria (LAB) are the common probiotics. Here, we investigated the antiviral protective effects of heat-killed LAB strain Lactobacillus casei DK128 (DK128) on influenza viruses. Intranasal treatment of mice with DK128 conferred protection against different subtypes of influenza viruses by lessening weight loss and lowering viral loads. Protection via heat-killed DK128 was correlated with an increase in alveolar macrophage cells in the lungs and airways, early induction of virus specific antibodies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
76
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 100 publications
(78 citation statements)
references
References 49 publications
2
76
0
Order By: Relevance
“…As described above, bacterial pathogens given prior to influenza viruses can stimulate innate immunity that reduces the severity of influenza (56,58). Infection of mice with nonpathogenic bacteria or with a parasite that causes a chronic infection has also been shown to reduce the severity of influenza infections (34,(62)(63)(64)(65). While the mechanisms of protection may differ among coinfecting microbes, protection relies on detection of the initial infection by pattern recognition receptors.…”
Section: Discussionmentioning
confidence: 99%
“…As described above, bacterial pathogens given prior to influenza viruses can stimulate innate immunity that reduces the severity of influenza (56,58). Infection of mice with nonpathogenic bacteria or with a parasite that causes a chronic infection has also been shown to reduce the severity of influenza infections (34,(62)(63)(64)(65). While the mechanisms of protection may differ among coinfecting microbes, protection relies on detection of the initial infection by pattern recognition receptors.…”
Section: Discussionmentioning
confidence: 99%
“…A closer evaluation of the role of AMs as both an independent source and a target of IL-6 in both pneumovirus and influenza infections might help to explain some of these divergent responses. It is also intriguing to note that the lethal sequelae influenza A can be limited by Lactobacillus at the respiratory mucosa (16)(17)(18)(19), results that suggest that AMs and IL-6 are not unique or universal targets of this immunomodulatory strategy.…”
Section: Discussionmentioning
confidence: 99%
“…14). Toward this end, we and others have found that administration of otherwise benign Lactobacillus species directly to the respiratory mucosa of virusinfected mice has resulted in protection against lethal disease (15)(16)(17)(18)(19). The mechanisms underlying this response and, more broadly, the ways in which bacteria, bacterial components, and pattern recognition receptor-activating ligands administered to the respiratory tract promote protection against lethal virus infection remain to be fully elucidated (20)(21)(22).…”
mentioning
confidence: 99%
“…The amounts of ginseng samples in the mixtures were in the range of 50–1000 µg doses per mouse. Then, 50 µL of virus–ginseng mixtures were intranasally inoculated into naive mice [ 19 , 20 ]. For the experiment involving treatment with ginseng after infection, wild-type BALB/c mice were infected with A/WSN (H1N1) influenza virus (1 × LD 50 ) first.…”
Section: Methodsmentioning
confidence: 99%